Neuro-Diplomacy In The Age Of Brain-Computer Interfaces: A Bibliometric Analysis Of Neural Networks, International Cooperation, And AI-Assisted Decision-Making - Irfan Maqbool (Corresponding Author) , Khalid Mahmood Awan , Muhammad Arslan , Dr. Madiha Khadim (Migration Letters, 2024)
This study offers a bibliometric review of research conducted between 2010 and 2024 on the emerging and rapidly expanding field of neuro-diplomacy, which explores the connections between brain-computer interfaces (BCIs), neural networks, international relations, and AI-driven decision-making. As advancements in neuroscience continue and artificial intelligence becomes more integrated into global affairs, neuro-diplomacy is poised to play an increasingly vital role in international relations. To investigate the trends, [1]influential publications, and gaps in the literature, this study utilized academic databases such as Google Scholar, PubMed, Scopus, Web of Science, and IEEE Xplore. The data analysis indicates a steady rise in the number of publications, reflecting growing interest in the application of BCIs and AI in diplomatic contexts. Through an examination of co-occurrences and citation patterns, the study identifies several key research areas, including the ethical considerations of neurotechnology, the role of AI in fostering international cooperation, and the use of neural networks to enhance decision-making processes. However, it also highlights the need for further research to fully understand the potential and limitations of neuro-diplomacy. By analyzing existing literature and exploring emerging trends, this study contributes to a deeper understanding of how BCIs and AI are reshaping diplomatic practices and international relations in the 21st century.